Recurrent herpes simplex of the index finger. - Mouhsine, Z.; El Fatoiki , F.E.; Hali, F.; Chiheb, S. (European Journal of Pediatric Dermatology, 2024)
A 6-year-old immunocompetent girl with no notable medical history was examined in the dermatology emergency room for a painful erosive lesion of the right index finger with periungual involvement. Physical examination highlighted an erythematous-erosive lesion with clustered, polycyclic pustules in the periphery (Fig. 1), associated with paronychia and pus secretion on pressure, without other associated cutaneous or extracutaneous signs. The mother had consulted several pediatricians and the child had been diagnosed with bacterial paronychia treated with oral amoxicillin-clavulanate without improvement. An additional history informed us that the child had had two similar episodes in the past on the same finger, which had regressed with fusidic acid, and that the child’s grandfather suffered from relapsing Herpes simplex of the lip. The mother also reported that the current erosion had been preceded by clustered vesicles. The Tzanck cytodiagnostic test showed balloon-like cells and the bacteriological examination was negative. The diagnosis of recurrent Herpes simplex was made, the child was treated with topical and oral acyclovir, and the mother was informed about possible recurrences.